Nushūz In Islamic Family Law: A Critical Study of Hadith Exegesis and Religious Court Verdicts - Kusmardani, Alex; Ahmad Fathonih; Usep Saepullah; Nurrohman (Mawaddah: Jurnal Hukum Keluarga Islam, 2024)
The ongoing family conflicts cannot be separated from the neglect of the position of the husband and wife in Islamic family law, known as nusūz. The purpose of this study is to understand Mufassireen's interpretation of nusyūz. This study is a qualitative research, a literature survey with an interdisciplinary approach - philosophical, Historical, psychological, sociological, and Islamic law approach - and a descriptive analysis from various sources such as tafsir, hadith, Islamic Yurisprudance, legal maxim and legislation. The meaning of nusyūz in al-Nisa 4:34 according to Mufassireen is similar. The difference between classical mufassirs and contemporary mufassirs is that classics allow and contemporary ones reject wife beating. There is also an interpretation of verse al-Nisa 128, where commentators argue that the husband's nusūz means relinquishing rights and obligations due to polygamy and unequal living, and the form of resolving the husband's nusūz is through advice and mediation. The judge's decision in resolving husband and wife nusu'us problems was the judge's reference to al-Baqarah paragraph 241, School Al-Dzahiriyah Article 39 paragraph 2 of Law Number 1 of 1974 concerning Marriage, Articles 149 and 241 Compilation of Islamic Law of 1991 as the implementation of takhsis al- qada is based on benefit which refers to the Islamic legal maxim Hukm al-Hakim Yarfa al-Khillaf, Tassaruf al-Imam Ra'iyah Ala Manut bi al-Maslahah.